Advancements and challenges in large molecule drug delivery and devices for patient-centric care - Mayumi Bowen; Yillma Adam; Debby Chang (AAPS Open, 2026)
Abstract Large molecule therapeutics, including monoclonal antibodies, recombinant proteins, and nucleic acids, offer precision and efficacy that have transformed the treatment of complex diseases such as autoimmune disorders, cancers, and genetic disorders. Despite their potential, their large size, structural complexity, and inherent biological instability create significant barriers to effective delivery, frequently necessitating invasive parenteral administration (e.g., intravenous, subcutaneous, or intramuscular routes). While effective, these traditional administration routes often require frequent healthcare visits, limiting accessibility, increasing the risk of administration errors, and affecting patient adherence. Recent advancements in formulation science and drug delivery device technologies—such as prefilled syringes, autoinjectors, wearable injectors, transdermal patches, and smart delivery systems—are enabling a paradigm shift toward patient-centric care. These innovations facilitate self-administration and home-based treatment, offering improved dose accuracy, greater convenience, and enhanced patient adherence. Furthermore, progress in formulation science, nanotechnology, innovative device technologies, and digital health is pioneering new minimally to non-invasive and direct delivery routes, such as pulmonary, transdermal, ophthalmic, and neurological approaches. Emerging trends like smart devices and sustainable practices are redefining therapeutic strategies, emphasizing effectiveness, accessibility, and personalized care. This mini-review explores the challenges of large molecule drug delivery, highlights advancements in formulation and device technology, and discusses emerging trends—including sustainable practices and digital health integration—that are shaping the future of patient-centric large molecule therapies.